Kajian Pengelolaan Sumber Daya Air Dalam Upaya Penyehatan Lingkungan Daerah Kejadian Luar Biasa Dusun Beran Desa Kanigoro Kecamatan Ngablak Kabupaten Magelang Tahun 2007 - Setiawan, Danny; Setiani, Onny; Hanani D., Yusniar (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background : Outbreak case in Kanigoro Village, Ngablak Sub District, Magelang Regency in July 2007 resulted in 31 victims and 10 people lost their lives with a symptom of being poisoned by toxic material. The condition of water sanitary system which did not meet health requirements was assumed as the cause. From the survey, it could be concluded that water used by the people was at high possibility of being polluted by pollutants because the distribution system did not meet requirements. Method : This research used a qualitative approach in order to find out various influences of the existing environmental sanitary conditions, the method used was survey (observation research) by conducting in-depth interview and observation by using questionnaires and check lists which had been composed, the sampling technique used was purposive sampling. The source of water for the people is Tuk Ngetuk Spring. The potential of water resource with a volume of 3.5 litres per second from quantity perspective has been able to meet the needs of Beran Hamlet’s people for the next 5 years. The risk factor for water pollution physically, bacteriological, and chemically had a value of high level of water pollution. Result : The finance for water resources management in an effort to sanitize the environment was so limited that influenced the infrastructure and the activity of watching water quality done by Health Service of Magelang Regency. Kanigoro Village’s head handed over the task and duty in managing water to his villagers, a person per hamlet respectively, who were being called ili-ili. The participation of the people in voluntary collective work activities every six months was hard to realize. Conclusion : To prevent water resources from being polluted with pesticide used in farming, there was a need for information given continually, the application of integral germ control, organic farming or biopesticide, and a building for catching water from the spring had to conform to the manual of practicing guide for capturing water from the spring. With regard to limited finance, there was a need for the empowerment of the people through the founding of a group of water users in Beran Water Reservoir Keywords: Water Resources, Management, Environmental Sanitation